Big book of bread : 125+ recipes for every baker - Battilana, Jessica; Philip, Martin; Wanders, Melanie; Anderson, Ed (Edward Charles) (Simon Element, an imprint of Simon & Schuster, LLC, 2024)
A bread book with 125 recipes that meet you where you are, whether novice or bread-head" --